The Knowledge, Self-Management, and Blood Glucose Control Among Patients with Type 2 Diabetes Mellitus: A Cross-Sectional Study - Nurmala Sari; Yarwin Yari; Ika Mustafida (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2026)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder characterized by elevated blood glucose levels and associated with a high risk of complications. Effective glycemic control is influenced by patients’ level of knowledge and their ability to perform self-management behaviors. This study aimed to examine the relationship between knowledge and self-management and blood glucose control among patients with Type 2 Diabetes Mellitus. Methods: This analytical quantitative study employed a cross-sectional design with a total sampling technique. A total of 83 patients with T2DM receiving treatment at Hospital were recruited. Inclusion criteria included adult patients diagnosed with T2DM, able to communicate effectively, and willing to participate in the study. Data were collected using the Diabetes Knowledge Questionnaire (DKQ-24), the Diabetes Self-Management Questionnaire (DSMQ), and medical record data. Blood glucose control was assessed based on random blood glucose (RBG) measurements documented in patients’ medical records. Data were analyzed using Spearman’s rank correlation test. Results: The majority of respondents had low levels of knowledge (50.6%) and moderate levels of self-management (72.4%). Spearman’s rank correlation analysis revealed a very strong negative correlation between knowledge and blood glucose control (r = −0.844, p < 0.001) and a strong negative correlation between self-management and blood glucose control (r = −0.675, p < 0.001). Conclusion: Better knowledge and optimal self-management were significantly associated with improved blood glucose control among patients with Type 2 Diabetes Mellitus. These findings highlight the importance of continuous diabetes education and self-management support programs to enhance glycemic control and reduce the risk of diabetes-related complications.